Holly Flechsig: capstone - Flechsig, Holly, artist (Colorado State University. Libraries, 2018)
The artist's statement: In the project, Moments, each painting represents an event in my life in which I changed or grew. I take into account the dimensions of canvas, the techniques I use, the materials, etc. to better define the memory the painting represents. As I have grown, my style has become more solidified. I believe that this is evident in the paintings show. To the audience, it is my goal to portray my experiences without giving away all the secrets of the paintings or myself.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting; fine art